Flexible and Stretchable Piezoresistive Sensor with Decoupled Pressure Sensing Capability - Kim, Wooseok; Kim, Doyoung; Kim, Jihwan; Park, Sang Uk; Lee, Hee Kyu; Joo, Janghoon; Lee, Se Gi; Chae, Jeong Woo; Kim, Jeonghyun; Han, Seungyong; Baac, Hyoung Won; Won, Sang Min (Advanced Materials Technologies, 2023)
Pressure sensors made on a mechanically deformable substrates are widely available for health monitoring systems, tactile sensors, and human–machine interfaces. While their sensitivity typically exceeds that of the human skin, it is highly challenging to perceive multiple kinds of mechanical inputs, such as normal, stretching, bending, and/or twisting forces, in a decoupled manner. For example, the interpretation of the specific pressure-related distortion requires differentiation of such pressure stimuli from the simultaneously measured mixed deformation. This report proposes a sensor with an engineered geometrical configuration that dramatically reduces its mechanical distortion made by non-pressure related stimuli. Such decoupled-sensing capability for normal force is characterized by a linear response of fractional resistance change at 2.07 kPa−1 and negligible responses to other deformations such as stretching and bending. An in vitro sensor demonstration for the diagnosis of stress urinary incontinence presents one mode of practical application of the sensor. Facile fabrication allows an interconnected array and wireless network to capture the spatial distribution of normal force and to record the data with consumer devices, respectively.
Keywords: Biophysical sensor; Conductive composites; Electro-mechanical sensors; Health monitoring system; Mechanical; Multimodal sensor; Normal forces; Piezoresistive sensors; Pressure sensing; Tactile sensors; biophysical sensors; conductive composites; electromechanical sensors; multimodal sensors; tactile sensors